HINDU ECO-PHILOSOPHY - Suwantana, I Gede (PANGKAJA, 2012)
Traditional Hindu environmental values and concerns have continued to influence the discourse and aligned practices of environmentalism in much of South Asia. Hinduism developed a strong moral ethos which to a large extent superseded the earlier (Vedic) view from the heavens (or of the gods) by a view as if,